Method for preparing high-silicon secondary pore zeolite by modifying natural STI zeolite

By performing multiple cycle grinding and dealumination-replenishing reactions on natural STI powder crystals, high-silicon STI zeolites with particle size less than 1 micron and silicon-aluminum ratio ≥20 were prepared, which solved the problems of poor thermal stability and large particle size of natural STI zeolites, and achieved efficient catalytic and adsorption performance improvement.

CN120398082APending Publication Date: 2025-08-01FUYU ZHANGJIAGANG NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510526150.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

Due to poor thermal stability, large particle size and low silicon-aluminum ratio, natural STI zeolites are difficult to be directly used in the field of catalysis or adsorption. The artificial synthesis of high silicon STI zeolites is high and it is difficult to synchronously optimize the pore structure.

Method used

Using ammonium fluorosilicate solution as the medium and microsphere zirconium oxide as the abrasive, natural STI powder crystals were subjected to multiple cycles in a sand mill, and combined with a dealuminum-replenishing reaction, a high-silicon STI zeolite microcrystalline material with a particle size of less than 1 micron and a silicon-aluminum ratio of ≥20 was prepared.

Benefits of technology

It has achieved the synchronous construction of grain nanoification, silicon-aluminum ratio improvement and secondary pore structure, which has enhanced the thermal stability and mass transfer efficiency of the material, and is suitable for macromolecular catalysis and adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398082A_ABST
    Figure CN120398082A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-silicon secondary pore zeolite by modifying natural STI zeolite. The method comprises the following steps: S1, taking an ammonium fluosilicate solution as a medium and microsphere zirconium oxide as a grinding material in a sand mill; s2, the NH4-STI powder crystal with the particle size being 13 microns and the SAR silicon-aluminum molar ratio being 6.0 is circularly ground and smashed for multiple times; and S3, simultaneously carrying out dealumination and silicon supplementation reaction to finally prepare the high-silicon STI zeolite microcrystalline material with the particle size of less than 1 micron and the SAR of more than or equal to 20. The preparation method has the advantages that the synthesis of a template agent is avoided, the raw material is natural ore, the cost is saved, the ammonium fluosilicate solution can be recycled, the discharge of waste liquid is reduced, the red zeolite resource can be efficiently developed, meanwhile, micropores keep shape selectivity and are suitable for macromolecule catalysis and adsorption, and the performance of the material in related applications is improved; and crystal grain nanocrystallization, silicon-aluminum ratio improvement and secondary pore structure construction are realized, the limitation of single function of traditional modification is broken through, and the material is optimized in multiple aspects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of natural STI zeolite, and particularly to a method for modifying natural STI zeolite to prepare high-silica secondary pore zeolite. Background Art

[0002] Natural STI zeolite ore is in the form of large crystals. Affected by geological formation reasons, natural STI zeolite is generally of the Ca type. Due to the slightly distorted pore structure of STI zeolite itself, its structural stability is closely related to the position and type of exchangeable cations during the dehydration process. The original Ca-type zeolite has the worst stability, and the framework is completely destroyed after calcination at 350 °C for 2 h, which limits its application in the fields of catalysis, adsorption, etc. Due to the special nature of the pore structure of STI zeolite itself, its artificial synthesis is difficult, and it has the following problems:

[0003] Limitations of natural STI zeolite: Natural STI zeolite is of the Ca type, with poor thermal stability (framework destruction at 350 °C), and the particle size of the ore powder obtained by mechanical crushing of the original ore is large (13 microns), and the silica-alumina ratio is low (SAR≈6), making it difficult to be directly used in the fields of catalysis or adsorption.

[0004] Bottlenecks in synthesizing high-silica STI: Synthesizing high-silica STI zeolite requires complex templates (such as quaternary ammonium salts), with high costs and the silica-alumina ratio being difficult to exceed SAR = 14; traditional modification methods can only increase the SAR to about 10, and cannot simultaneously reduce the grain size.

[0005] Application limitations: The particle size of the existing modified STI zeolite is still large (13 microns), and it needs to be further nano-sized in catalyst applications; traditional mechanical grinding only crushes the grains and cannot simultaneously optimize the pore structure.

[0006] Therefore, we propose a method for modifying natural STI zeolite to prepare high-silica secondary pore zeolite to solve the above problems. Summary of the Invention

[0007] The purpose of the present invention is to solve the drawbacks existing in the prior art, and to propose a method for modifying natural STI zeolite to prepare high-silica secondary pore zeolite.

[0008] To achieve the above purpose, the present invention adopts the following technical scheme:

[0009] A method for modifying natural STI zeolite to prepare high-silica secondary pore zeolite, comprising the following steps:

[0010] S1. Using ammonium fluorosilicate solution as the medium and zirconia microspheres as the abrasive in a sand mill;

[0011] S2. Conducting multiple cyclic grinding and pulverization on NH4-STI powder crystals with a particle size of 13 microns and a silica-alumina molar ratio (SAR) of 6.0;

[0012] S3. Simultaneously carry out dealumination and silica supplementation reactions to finally obtain a high-silica STI zeolite microcrystalline material with a particle size less than 1 μm and SAR≥20.

[0013] Preferably, the number of cyclic grinding times is 7, and the SAR of the final product can reach 22.7.

[0014] Preferably, the mass ratio of the grinding medium to the raw material powder is 1:1 to 4:1.

[0015] Preferably, the grinding temperature is controlled below 45°C.

[0016] Preferably, the NH4-STI raw material powder is obtained by subjecting natural STI ore powder to three ammonium chloride exchanges.

[0017] Preferably, the high-silica STI zeolite microcrystalline material has a micropore diameter of 0.47 - 0.50 nm and a mesopore diameter of 8 - 10 nm.

[0018] The present invention has the following advantages:

[0019] 1. Directly utilize natural STI ore, avoid complex synthesis processes, and reduce raw material costs;

[0020] 2. Simultaneously achieve grain nanocrystallization (<1 μm), increase in silicon-aluminum ratio (SAR≥20), and secondary pore structure (micropores + mesopores), breaking through the limitations of single functions in traditional modification;

[0021] 3. Mesopores (8 - 10 nm) enhance mass transfer efficiency, and micropores (0.47 - 0.50 nm) maintain shape selectivity, being suitable for macromolecular catalysis and adsorption;

[0022] 4. The silicon-aluminum ratio is increased from SAR = 6 to 22.7, enhancing acid stability and thermal stability;

[0023] 5. The pore volume increases from 0.128 cm 3 / g to 0.288 cm 3 / g, and the average pore diameter expands from 2.54 nm to 7.4 nm, improving the diffusion efficiency of macromolecules;

[0024] 6. The grain size decreases from 13 μm to <1 μm, increasing the surface active sites;

[0025] In summary, the present invention eliminates the synthesis template agent, uses natural ore as the raw material, saves costs, enables the recycling of ammonium fluorosilicate solution, reduces waste liquid discharge, efficiently develops the unique red zeolite resources in China, enhances the mass transfer efficiency, maintains the shape selectivity of micropores, is suitable for macromolecular catalysis and adsorption, improves the performance of the material in related applications, simultaneously realizes grain nanocrystallization, silicon-aluminum ratio increase and secondary pore structure construction, breaks through the limitation of traditional single-function modification, and optimizes the material in multiple aspects. Description of the Drawings

[0026] Figure 1 It is a schematic diagram of the STI zeolite framework structure;

[0027] Figure 2 It is an SEM image of the STI ore powder after being processed 7 times by the grinding, pulverizing and cyclic silicon supplementation method of the present invention;

[0028] Figure 3 It is the particle size distribution diagram of the NH4-STI particles after being processed by the grinding, pulverizing and cyclic silicon supplementation method of the present invention;

[0029] Figure 4 It is the XRD powder diffraction pattern of the NH4-STI ore powder after being processed by the grinding, pulverizing and cyclic silicon supplementation method of the present invention;

[0030] Figure 5 It is the low-temperature nitrogen adsorption isotherm of the product of the first cycle of grinding;

[0031] Figure 6 It is the low-temperature nitrogen adsorption / desorption isotherm of the products of the second, third and fourth cycles of grinding;

[0032] Figure 7 It is the low-temperature nitrogen adsorption / desorption isotherm of the products of the fifth, sixth and seventh cycles of grinding. Detailed Embodiments

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.

[0034] A method for modifying natural STI zeolite to prepare high-silica secondary pore zeolite, and its testing method is as follows:

[0035] 1.1, SEM observation of crystal particles

[0036] The NH4-STI zeolite sample treated by the grinding, pulverizing and cyclic silicon supplementation method of the present invention was observed and photographed with a PhenomProx desktop scanning electron microscope from Phenom Company in the Netherlands.

[0037] 1.2, XRD crystal phase identification

[0038] The crystal phase of the NH4-STI zeolite sample treated by the grinding, pulverizing and cyclic silicon replenishing method of the present invention was determined by an XD2 type X-ray powder diffractometer of Beijing Purkinje General Instrument Co., Ltd., with a scanning range of 5-35° / 2θ and a scanning speed of 4° / 2θ / min.

[0039] 1.3, Chemical composition determination

[0040] The percentage contents of SiO2, Al2O3, K2O, Na2O, Fe2O3, CaO, and MgO of the NH4-STI zeolite sample treated by the grinding, pulverizing and cyclic silicon replenishing method of the present invention were determined by an S8 TIGER X-ray fluorescence scattering instrument (XRF) of Bruker Co., Germany, and its silicon-aluminum molar ratio (SAR) was calculated.

[0041] 1.4, Low-temperature nitrogen adsorption

[0042] The BET specific surface area of the natural STI zeolite sample treated by the grinding, pulverizing and cyclic silicon replenishing method of the present invention was determined by a 3H-2000PS2 static volumetric specific surface and pore size analyzer of Beijing Beishide Instrument Co., Ltd.

[0043] 1.5, Particle size determination

[0044] The crystal grain size of the NH4-STI zeolite sample treated by the grinding, pulverizing and cyclic silicon replenishing method of the present invention was determined by a BT-9300ST type Bettersize laser particle size distribution analyzer of Dandong Bettersize Instruments Co., Ltd.

[0045] 2 Grinding, pulverizing and cyclic silicon replenishing of NH4-STI powder

[0046] The equipment used for the NH4-STI zeolite sample treated by the grinding, pulverizing and cyclic silicon replenishing method of the present invention is a sand mill of model CDS-2, with an effective volume of 1 liter. The grinding medium used is pure zirconia beads, with a dosage of 6 kg. The grinding temperature is controlled within 45 degrees.

[0047] An ammonium fluorosilicate solution with a concentration of 2.2 mol was prepared as the grinding medium in an 8-liter stainless steel container (Container I). NH4-STI prepared from 1000-mesh (13 μ) STI natural ore powder after 3 times of ammonium chloride exchange was used as the raw material powder for the grinding, pulverizing and cyclic silicon replenishing method of the present invention. The two were mixed, and the ratio of the grinding medium to the ore powder was between 1 and 4. After the mixture was pumped into the sand mill, the motor of the sand mill was started for the first cycle of grinding. The ground mixture was stored in another 8-liter stainless steel container (Container II) to complete the first cycle of grinding. A small amount of the mixture after the first cycle of grinding was extracted from Container II, separated from the zirconia bead abrasive therein, and the remaining slurry was filtered, washed and dried into a dry powder. The NH4-STI dry powder obtained from the first cycle of grinding was subjected to the following physical property tests:

[0048] 1. Observed and photographed with a PhenomProx benchtop scanning electron microscope from Phenom, Netherlands (see Figure 1 );

[0049] 2. Determined the volume distribution and weight distribution of its particle size with a BT-9300ST Bettersize laser particle size analyzer, see Figure 3 ;

[0050] 3. Identified its crystal phase with an XD2 X-ray powder diffractometer, and its XRD diffraction pattern is shown in Figure 4 ;

[0051] 4. Determined its chemical composition with an S8 TIGER X-ray fluorescence scattering instrument (XRF), and the data are listed in Table 1;

[0052] 5. Measured its low-temperature nitrogen adsorption isotherm and pore property data with a 3H-2000PS2 static volumetric method specific surface and pore size analyzer, and the results are shown in Figure 5 and Table 2 respectively.

[0053] The mixture stored in Container II after the first cycle of grinding (containing zirconia abrasive, ammonium fluorosilicate solution as grinding medium, and NH4-STI ore powder after the first cycle of grinding) was continuously put into a CDS-2 sand mill for the second cycle of grinding. Samples were also taken for particle size analysis during this period, and the results are shown in Figure 3 , and the measured XRD diffraction pattern is shown in Figure 4 ; The XRF composition test data are listed in Table 1; The test results of its low-temperature nitrogen adsorption isotherm and pore property data are shown in Figure 5 , Figure 6 and Figure 7 respectively.

[0054] The relevant tests on the NH4-STI samples after the 3rd cycle of grinding, the 4th cycle of grinding, the 5th cycle of grinding, the 6th cycle of grinding, and the 7th cycle of grinding were obtained with the same operation and sampling sequence and are summarized in Table 1, Table 2, and Figure 3 , Figure 4 , Figure 5 respectively.

[0055] 3. Particle size distribution of the cyclic silicon-supplemented product of grinding and pulverization

[0056] From Figure 3From the particle size analysis results graph, it can be seen that as the number of grinding and pulverizing cycles gradually increases from 1 to 7, the peak value of the particle size of the grinding and pulverizing cycle processed product powder approaches gradually from about 10 μm to about 1 μm both in terms of its volume distribution and its number distribution. This fact shows the good effect of using the CDS-2 type sand mill to pulverize NH4-STI zeolite powder. Observation and taking photos were carried out with a PhenomProx type bench-top scanning electron microscope (see Figure 1 ). It can be seen that the particle size of the NH4-STI zeolite powder after 7 grinding and pulverizing cycles is significantly less than 1 μm.

[0057] 4. Phase identification of the grinding and pulverizing cycle silicon-supplemented product

[0058] From Figure 4 the XRD pattern, it can be seen that the product powder processed by the grinding and pulverizing cycle silicon-supplemented method still maintains the typical XRD pattern of STI zeolite. However, as the number of cycles increases, the baseline of the XRD spectrum of the grinding and pulverizing cycle silicon-supplemented product rises upward in the 2θ range of diffraction angles from 20 to 30 degrees. This may be due to the fact that grinding destroys the crystal structure of part of the NH4-STI powder and produces diffraction of amorphous substances.

[0059] 5. Composition of the grinding and pulverizing cycle silicon-supplemented product

[0060] The chemical composition data of the NH4-STI powder processed by the grinding and pulverizing cycle silicon-supplemented method of the present invention are listed in Table 1. It can be seen that as the number of grinding and silicon-supplemented cycles increases, the dealumination and silicon-supplementation effect of the ammonium fluorosilicate solution causes the aluminum content of the ground NH4-STI powder to gradually decrease, and the SAR gradually increases. The SAR of the STI powder obtained by the seventh grinding exchange increases gradually from 5.53 of its raw material NH4-STI powder to 22.70.

[0061] Table 1. Chemical composition of the STI ore powder processed by the grinding and pulverizing cycle silicon-supplemented method of the present invention

[0062]

[0063]

[0064] The raw material NH4-STI powder used for the grinding and pulverizing cycle silicon-supplemented method of the present invention was prepared by subjecting 1000-mesh (13 μ) STI natural ore powder to 3 ammonium chloride exchanges

[0065] 6. Pore properties of the grinding and pulverizing cycle silicon-supplemented product

[0066] After the NH4-STI processed by the grinding and pulverizing cycle silicon-supplemented method of the present invention is calcined at 350 °C to remove ammonia, the low-temperature nitrogen adsorption isotherm and pore adsorption data are measured by the 3H-2000PS2 static volumetric method specific surface area and pore size analyzer of Beijing Bettersize Instruments Ltd. and are respectively shown inFigure 5 , Figure 6 and Figure 7 Table 2

[0067] Figure 5 is the low-temperature nitrogen adsorption isotherm of the product of the first-cycle grinding. It can be seen that its adsorption capacity is very low, and the adsorption capacity slowly increases to about 24 ml / g as the partial pressure gradually increases. Moreover, its desorption isotherm coincides with the adsorption isotherm, indicating that the pores of this sample are completely open.

[0068] Figure 6 are the low-temperature nitrogen adsorption / desorption isotherms of the products of the 2nd, 3rd, and 4th cycle grindings. It can be seen that they are all typical type-I micropore adsorptions. The adsorption capacities at the nitrogen partial pressure P / P0 = 0.1 are about 8 ml / g, 18 ml / g, and 32 ml / g respectively, indicating that as the number of cycle grindings increases, the micropore adsorption performance of the product becomes more and more obvious. Moreover, there are very obvious hysteresis loops between the desorption isotherm and the adsorption isotherm in the range of P / P0 = 0.10 to P / P0 = 0.99 for the low-temperature nitrogen adsorption / desorption isotherms of these three-cycle grinding products, which indicates that the STI zeolite products processed by the 2nd, 3rd, and 4th cycle grindings form mesopores with a relatively wide pore size distribution.

[0069] Figure 7 are the low-temperature nitrogen adsorption / desorption isotherms of the products of the 5th, 6th, and 7th cycle grindings. It can be seen that they are all typical type-I micropore adsorptions. The adsorption capacities at the nitrogen partial pressure P / P0 = 0.1 are about 37 ml / g, 45 ml / g, and 46 ml / g respectively, indicating that as the number of cycle grindings increases, the micropore adsorption performance of the product becomes more and more obvious. Moreover, there are very obvious hysteresis loops between the desorption isotherm and the adsorption isotherm in the range of P / P0 = 0.60 to P / P0 = 0.99 for the low-temperature nitrogen adsorption / desorption isotherms of these three-cycle grinding products, which is caused by the formation of mesopores with a relatively large pore size in the STI zeolite products processed by the 5th, 6th, and 7th cycle grindings.

[0070] To compare the H-STI prepared by the cyclic grinding silicon supplementation method of the present invention with the traditional method, that is, the product H-STI after calcination at 350 °C of NH4-STI generated by three-time ammonium chloride exchange of 1000-mesh STI ore powder * for the comparison of the measured low-temperature nitrogen adsorption data (see the first column of Table 2 for H-STI * data), the following phenomena can be found:

[0071] Phenomenon 1, the BET surface area and micropore specific surface area of the H-STI *y sample are as high as 448 m 2 g -1 and 392 m 2 g -1, the total pore volume and micropore volume are 0.284 cm 3 g -1 and 0.156 cm 3 g -1, respectively, and the average pore diameter is 2.54 nm, showing the pore properties of a typical microporous molecular sieve. However, for NH4-STI processed multiple times by the cyclic grinding and silicon supplementation method of the present invention, samples were taken after each cyclic grinding and calcined at 350 °C to remove ammonia to obtain H-STI, and its pore properties changed significantly. The BET and Langmuir specific surface areas, T-Plot micropore volume, and T-Plot micropore specific surface area data were all significantly lower than the corresponding data of the comparative H-STI * sample, while the total pore volume, mesopore volume, and average pore diameter showed an increase with the increase in the number of cyclic processing times and were significantly higher than the corresponding data of the H-STI* zeolite sample.

[0072] Phenomenon 2: Intense grinding and the simultaneous dealumination and silicon supplementation reaction cause fundamental changes in the pore structure of the STI zeolite while the particle size of the STI zeolite decreases and the product SAR increases from a low-silica STI zeolite with an SAR of about 6 to a high-silica STI zeolite with an SAR of about 20. Its average pore diameter suddenly increases from 2.5 nm micropores to mesopores of about 6 nm to about 10 nm; this phenomenon proves that the large-grained microporous low-silica STI zeolite is modified by the cyclic grinding and silicon supplementation method into a novel microcrystalline microporous / mesoporous hierarchical pore high-silica STI zeolite. This modified high-silica STI zeolite new material is expected to develop new applications in catalysis and adsorption separation.

[0073] Table 2 Cyclic grinding exchange times - product pore property table of the present invention

[0074]

[0075]

[0076] H-STI after calcination at 350 °C of NH4-STI generated by three ammonium chloride exchanges of 1000-mesh STI ore powder.

[0077] As mentioned above, it is only the preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and all should be covered within the protection scope of the present invention.

Claims

1. A method for preparing high-silica secondary pore zeolite by modifying natural STI zeolite, characterized in that, It includes the following steps: S1. Using ammonium fluorosilicate solution as the medium and microsphere zirconia as the abrasive in a sand mill; S2. Conducting multiple cyclic grinding and pulverization on NH4-STI powder crystals with a particle size of 13 microns and an SAR silicon-aluminum molar ratio of 6.0; S3. Simultaneously carrying out dealumination and silicon supplementation reactions to finally obtain high-silica STI zeolite microcrystalline materials with a particle size less than 1 micron and SAR≥20.

2. The method for preparing high-silica secondary pore zeolite by modifying natural STI zeolite according to claim 1, characterized in that, The number of cyclic grinding times is 7, and the SAR of the final product can reach 22.

7.

3. A method for preparing high-silica secondary pore zeolite by modifying natural STI zeolite according to claim 1, characterized in that, The mass ratio of the grinding medium to the raw material powder is 1:1 to 4:

1.

4. A method for preparing high-silica secondary pore zeolite by modifying natural STI zeolite, characterized in that, The grinding temperature is controlled below 45°C.

5. A method for preparing high-silica secondary pore zeolite by modifying natural STI zeolite according to claim 1, characterized in that, The NH4-STI raw material powder is obtained by subjecting natural STI ore powder to three ammonium chloride exchanges.

6. The method for preparing high-silica secondary pore zeolite by modifying natural STI zeolite according to claim 1, characterized in that The high-silica STI zeolite microcrystalline material has a micropore aperture of 0.47 - 0.50 nm and a mesopore aperture of 8 - 10 nm.